Seorang Wanita Usia 63 Tahun Dengan Penurunan Kesadaran, Struma Nodusa Hipertiroidisme, CHF NYHA IV, Dan Pneumonia - Sri Meutia; Khairunnisa Syahril (Jurnal Anestesi, 2023)
Hypertiroidism that continues into a thyroid storm is one of the rarest complication to be found in Indonesia. The pathogenesis of thyroid storm hasn’t been identified, but this condition is suspected as a result of the free thyroid hormones that escalates after a thyroidectomy or I-131 therapy, infection, acute stress, non-tiroid surgery, parturition, and overmanipulated thyroid glands. Thyroid storm is an emergency condition that can happened to a hyperthyroidism patients that needs a specific and fast management. If this condition is being treated correctly, the mortality rate of patient could be decreased, therefore a case of a 63 years old woman with the loss of consciousness with hyperthyroidism goiter node as the trigger factor that leads into a thyroid storm, happens with a congestive heart failure and pneumonia. The assessment with Burch-Wartofsky obtained a score of 55, then treated with the right diagnostic assessment and treatment. After the treatment, that patient’s condition was getting better day by day, but the patient’s family later decided to bring the patient home in the third day of treatment.